THE ANALYSIS OF PATIENT RESPONSES AFTER SALES SERVICE ON HEALTH CENTER (PUSKESMAS) TELING ATAS MANADO - To, Anggi; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Health is the most important thing that must be maintained by all persons in the world. The health of the people also can do their activities well and health development should be seen as an investment to improve the quality of human resources. Puskesmas is one of the two health services needed by the community in Indonesia. The main objective of this study is to analyze the Importance and Performance of patient responses after sales service using Importance Performance Analysis on Health Center (Puskesmas Teling Atas) Manado. The type of this research is descriptive quantitative methods by using Importance-Performance Analysis (IPA) as the analytical tool. Â Puskesmas Teling Atas Manado has been chosen as population for the study. This research took 100 respondents in this case is patient as the sample. The result of this study show customers expectation is low importance and the high importance, perceived service and overall service quality are important and good performance, and behavioral intention is low performance and low importance on Puskesmas Teling Atas Manado. The employees have to maintained the quality of the service to make the patients more comfortable and satisfied. Keywords: service quality, after sales service, important performance analysis.